COMPARISON OF NUMBER OF DIFFUSION GRADIENT DIRECTION IN BRAIN IMAGING DIFFUSION TENSOR; CASE STUDY OF TUMOR BRAIN - Rofiky, Afif; Rahardjo, Paulus; Soeharmanto, Didik (Faculty of Vocational Studies, Universitas Airlangga, 2017)
Background: Diffusion Tensor Imaging (DTI), namely MRI sequence which is the diffusion of water analysis that shows the complex structure of brain tissue. The weakness of this sequence is scanning time. Number of Diffusion Gradient Direction (NDGD) is one of parameter that effect scanning time. Purpose: This study has aim to compare between NDGD 25 and NDGD 15 in brain tumor. Method: This study used observational analytic study with prospective approach. Five patients were examined using DTI sequence with NDGD 25 and NDGD 15. The parameter for evaluating the quality image is of Fractional Anisotropy (FA) and Fiber Tracking (FT). Result: Image with NDGD 25 was better than NDGD 15, but the difference was not significantly. Conclusion: It can be concluded that NDGD 15 can be solution to get informative image with short scan time when DTI sequence is used to examine brain tumor.